Interaction styles and input/output devices. - Jacob, Robert J. K.; Leggett, John J.; Myers, Brad A. (Brad Allan); Pausch, Randy. (Tufts University. Tisch Library., 2017)
This is an Accepted Manuscript of an article published by Taylor & Francis in Behaviour & Information Technology in Vol 12, Iss 3 (1993), available online: http://www.tandfonline.com/10.1080/01449299308924369.